Pengaruh Terapi Isometric Handgrip terhadap Tekanan Darah pada Lansia di Wilayah Kerja Puskesmas Dungaliyo - Dewi Anggraini Abas; Rona Febriyona; Andi Nur Aina Sudirman; Inne Ariane Gobel (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension often does not cause obvious clinical symptoms, but the mortality rate caused by this condition, especially in the elderly, is quite high. Therefore, effective treatment strategies are needed, one of which is through the use of non-pharmacological isometric handgrip therapy. This study was conducted with the aim of analyzing the effect of isometric handgrip therapy on blood pressure in the elderly in the Dungaliyo Community Health Center Work Area. The type of research applied was quantitative with a pre-experimental design through a one-group pre-post test design approach. Sample selection was carried out using a purposive sampling technique involving 36 elderly respondents according to the inclusion criteria. The data collection instrument used an observation sheet to record the results of systolic and diastolic blood pressure measurements before and after. The intervention procedure was carried out routinely for five consecutive days. The study findings revealed that before therapy, the majority of respondents were in stage I hypertension. After the intervention, there was a decrease in average systolic blood pressure by 15.44 mmHg and diastolic by 11.30 mmHg, resulting in most respondents shifting to the high normal category. The Wilcoxon statistical test results confirmed a highly significant effect, with a p-value of 0.000 < 0.005. In conclusion, isometric handgrip therapy has been proven effective in lowering blood pressure and can be an appropriate non-pharmacological, preventive, and promotive approach for the elderly. It is recommended to optimize the regular implementation of this therapy and expand education regarding healthy lifestyle modifications and hypertension screening and management in the elderly.